Intrinsic functional neuron-type selectivity of transcranial focused ultrasound neuromodulation - Yu, Kai; Niu, Xiaodan; Krook-Magnuson, Esther; He, Bin (Nature communications, 2021)
Transcranial focused ultrasound (tFUS) is a promising neuromodulation technique, but its mechanisms remain unclear. We hypothesize that if tFUS parameters exhibit distinct modulation effects in different neuron populations, then the mechanism can be understood through identifying unique features in these neuron populations. In this work, we investigate the effect of tFUS stimulation on different functional neuron types in in vivo anesthetized rodent brains. Single neuron recordings were separated into regular-spiking and fast-spiking units based on their extracellular spike shapes acquired through intracranial electrophysiological recordings, and further validated in transgenic optogenetic mice models of light-excitable excitatory and inhibitory neurons. We show that excitatory and inhibitory neurons are intrinsically different in response to ultrasound pulse repetition frequency (PRF). The results suggest that we can preferentially target specific neuron types noninvasively by tuning the tFUS PRF. Chemically deafened rats and genetically deafened mice were further tested for validating the directly local neural effects induced by tFUS without potential auditory confounds. Low-intensity transcranial focused ultrasound (tFUS) is a non-invasive neuromodulation technique with high spatial specificity. The authors show that excitatory and inhibitory neurons respond differently to tFUS, suggesting the possibility of preferentially targeting specific neuron types via noninvasive tFUS.